CFD modeling of performance enhancement for nuclear research reactor cooling system - Darmawan, Rosli (2015)
The Reactor TRIGA PUSPATI (RTP), a pool-type research reactor started operation in 1982 with maximum steady state power of 1 MW is classified as a low flux research reactor with very limited applications. Many of such reactors have undertaken upgrading exercises to increase the capacity which involved the installation of higher capacity heat removal system. This approach requires higher cost as well as major modification of the reactor pool. Other alternatives which require less modification have been investigated. The RTP cooling pool operates on normal water at 32oC bulk temperature in laminar flow steady state condition, surrounded by adiabatic wall, floor and open top exposes to room temperature. The heat source comes from the reactor core at 550W/m2 heat flux and cooled down by natural convection. These conditions were modeled using CFD computational code FLUENT V6.3. The conservation equations for fluid flow, momentum, continuity and energy equation were solved numerically to predict the hydrodynamic and thermal behaviors of the model. The modeling of natural convection employed Boussinesq approximation model for the buoyancy term to achieve faster convergence. A prototype of 1/10th scale model was developed to verify the simulation results. A dimensional analysis using Buckingham  theorem was conducted to develop a dimensionless correlation to characterize the system and to ensure the geometric and kinematic similarity of the model. The simulation results showed similar temperature and velocity profiles with similar cases available in the literature. The measured data from the scaled model and the CFD simulation showed good agreement. The results reveal the flow regimes, temperature profile and the mechanism of the natural convection formation inside the reactor cooling pool. Four (4) cooling optimization techniques were simulated at normal operating heat flux (550W/m2 ) and at higher heat flux of 1100W/m2 and 1650W/m2 to assess its cooling performance. The results show that the installation of in-pool pumps, conduction rods and low temperature cooling inside the existing pool system may be able to enhance the cooling capacity up to 1.5 to 3 times the normal heat flux; whereas the installation of in-pool heat exchanger only performed slightly better than normal operation.